PENGARUH ONLINE CUSTOMER REVIEW DAN PERCEIVED VALUE TERHADAP KEPUASAN KONSUMEN SCARLETT WHITENING PADA MARKETPLACE SHOPEE - Nazwa Siti Laila Septianti; Ahmad Johan; Adi Praptika Jaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of Online Customer Reviews and Perceived Value on Consumer Satisfaction of Scarlett Whitening products in the Shopee marketplace. The study uses a quantitative method with a descriptive and verification approach. The research sample consisted of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of IBM SPSS. The results of the study indicate that Online Customer Reviews and Perceived Value are in the high category and have a positive and significant effect on Consumer Satisfaction, both partially and simultaneously. The coefficient of determination (R²) value of 0.512 indicates that both variables can explain 51.2% of the variation in Consumer Satisfaction, while 48.8% is influenced by other factors outside the study. These results indicate that the better the customer reviews and the higher the perceived value of consumers, the higher the level of Consumer Satisfaction with Scarlett Whitening products in the Shopee marketplace.